2018
DOI: 10.1097/ogx.0000000000000610
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Clinical Efficacy of Vaginal Progesterone for Luteal Phase Support in Assisted Reproductive Technology Cycles

Abstract: (Abstracted from Reprod Biomed Online 2018;36:630–645) Sufficient luteal phase support (LPS) is essential during assisted reproductive technology (ART) cycles to improve implantation and pregnancy rates. The most common route for LPS in Europe is vaginal progesterone via capsule, gel, or tablet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Our systematic review found seven articles evaluating effects of progesterone in second or third trimester for preterm birth prevention, and however, no RCTs evaluated effects of progesterone in first trimester for luteal phase support. Progesterone is frequently employed for this indication, with over 90% of ART cycles worldwide reporting the use of progesterone as luteal phase support in 2013 5 . More importantly, trials evaluating progesterone as luteal phase support in ART generally consider ongoing pregnancy or live birth rate as primary outcome(s), with limited neonatal outcomes reported 4,5,46 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our systematic review found seven articles evaluating effects of progesterone in second or third trimester for preterm birth prevention, and however, no RCTs evaluated effects of progesterone in first trimester for luteal phase support. Progesterone is frequently employed for this indication, with over 90% of ART cycles worldwide reporting the use of progesterone as luteal phase support in 2013 5 . More importantly, trials evaluating progesterone as luteal phase support in ART generally consider ongoing pregnancy or live birth rate as primary outcome(s), with limited neonatal outcomes reported 4,5,46 .…”
Section: Discussionmentioning
confidence: 99%
“…International guidelines advise progesterone as luteal phase support for assisted reproductive technologies (ART) and for preterm birth prevention. The exact percentage of pregnancies in which progesterone is employed is estimated at 5-12% of all pregnancies (around 2-3% of babies are born through ART in western countries 5 and the incidence of preterm birth is 5-12%). 44,45 The expanding list of indications for progesterone in pregnancy have led to growing numbers of children being exposed to progesterone at various stages of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison between vaginal/rectal and IM-P routes in the updated Cochrane meta-analysis reported no difference in LBR (4 RCTs, 1, 222 patients, OR 1.17, 95 % CI 0.91 to 1.51) [7]. A recent systemic review of 18 trials comparing 4 vaginal P products have shown that there are no significant differences in efficacy or safety between the products [38].…”
Section: Vaginal Progesteronementioning
confidence: 99%
“…Progesterone used for luteal phase support (derived from several species of Dioscorea, widely known as the yam plant [9]) can be formulated for intramuscular, oral, subcutaneous, or vaginal administration [10][11][12][13]. No progesterone formulation has, as yet, been shown to be superior in terms of efficacy [8,14,15], while tolerability and safety profiles vary according to the route of administration [10]. For example, although easier for the patient to use, orally administered micronized progesterone is rapidly metabolized by the liver and is associated with drowsiness, flushing, and nausea [10].…”
Section: Introductionmentioning
confidence: 99%